Models of the Effects of Ultraviolet Exposure, Temperature, and Humidity on the Quantity of Microplastics in Indoor Air - Mulyasari, Tri Marthy; Nur Hilal; Teguh Widiyanto; Lagiono (Window of Health : Jurnal Kesehatan, 2025)
Microplastics are a new pollutant in the air, but the determination of the maximum limit of their existence has not been set in regulations. Microplastics found in the air of building spaces are made from plastic waste. The presence of microplastics in the air is influenced by physical environmental factors. Inhaling microplastics can have a detrimental impact on lung tissue. The research aims to create a mathematical model of the effect of ultraviolet exposure, temperature, and humidity on the quantity of microplastics in indoor air. Mathematical models can be used to predict the quantity of microplastics in the air. The type of research is a true experiment with a posttest-only control group design. Air samples are taken daily for 60 days by the passive method by taking dustfall. The parameters measured include the quantity of microplastics, ultraviolet intensity, temperature, and air humidity. Microplastic examination by visual method using a 40-fold magnification binocular microscope. Analysis of the mathematical model of the effect of ultraviolet exposure, temperature, and humidity on the quantity of microplastics in the form of time series data using linear regression. The results of data analysis show that the effect of the panel regression estimation model, in accordance with the empirical data, is the Fixed Effect Model (FEM). The conclusion based on the results of the study shows that physical environmental factors have an influence on the quantity of microplastics in the air, whose existence can be predicted using FEM modeling that has been made.